The Honeysuckle cookbook : 100 healthy, feel-good recipes to live deliciously - Lewis, Dzung; Thomson, Jess (Rodale Books, an imprint of Random House, a division of Penguin Random House LLC, 2020)
"The Honeysuckle Cookbook is stuffed with new ideas for easy, approachable Asian-influenced cooking at home. With 90 recipes, from the breakfast favorites that consistently rate the highest in views on the author's YouTube channel (like her Overnight Oats, 6 Ways) to original twists on one-pan and pressure-cooker meals, this book is for seriously busy young professionals who want crave-worthy Asian meals made simple. Her food takes the familiar and turns it ever-so-slightly on its head : marinara sauce gets extra umami with the addition of fish sauce, while mac and cheese becomes much more than an out-of-the-box staple when made fresh with kimchi. Dzung also teaches readers how to stretch groceries so they spend a little less money, how to plan meals seasonally, and shows new cooks how to match main courses with sides, so plates look impressive and taste great. With time-saving snack ideas, recipe hacks, foolproof instructions, and genius tips for pretty presentation, The Honeysuckle Cookbook will be the friendly hand busy young cooks need to hold in the kitchen"--